2019
DOI: 10.1021/acscatal.9b02842
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Photocatalytic Valorization of Lignin Model Compounds Using Ultrathin Metal/CdS

Abstract: Depolymerization of recalcitrant lignin is a crucial step in realizing the full potential of transforming biomass to value-added small organic molecules. Herein, we report a photocatalytic system consisting of ultrathin CdS nanosheets decorated with first-row transition metals (M/CdS) for the direct photocleavage of lignin model compounds to small aromatic products. In the meantime, the reducing power of M/CdS is utilized to simultaneously generate another valuable product, H2, hence eliminating the necessity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 38 publications
0
99
0
Order By: Relevance
“…Photocatalytic lignin depolymerization has attracted increasing attention in recent years because of its mild reaction conditions, simple reaction process, and great environmental friendliness [ 80 , 81 ], making it a potential method for replacing the traditional process of lignin depolymerization. The electrons in the photocatalyst are brought into their excited state by light, which may substitute reductants, and each electron transition will produce a hole that may substitute oxidants [ 82 , 83 ].…”
Section: Recent Advances In Lignocellulosic Biomass Treatment Processesmentioning
confidence: 99%
“…Photocatalytic lignin depolymerization has attracted increasing attention in recent years because of its mild reaction conditions, simple reaction process, and great environmental friendliness [ 80 , 81 ], making it a potential method for replacing the traditional process of lignin depolymerization. The electrons in the photocatalyst are brought into their excited state by light, which may substitute reductants, and each electron transition will produce a hole that may substitute oxidants [ 82 , 83 ].…”
Section: Recent Advances In Lignocellulosic Biomass Treatment Processesmentioning
confidence: 99%
“…The spatially ordered heterojunction structure formed between TiO 2 and γ‐Fe 2 O 3 , as well as an incorporation of Fe 3+ into TiO 2 , enhanced the photocatalytic activity and selectivity of TiO 2 by increasing its light absorption and decreasing its band gap energy . Sun and co‐workers synthesized a series of first‐row transition metal/CdS nanosheets, including Mn, Fe, Co, Ni, and Cu supported on CdS, for the photocatalytic oxidation and degradation of lignin models . They revealed that Ni/CdS not only showed excellent catalytic performance for conversion of lignin into aromatic products in high yields but also simultaneously promoted H 2 evolution under visible light irradiation …”
Section: Catalysts For Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…Sun and co‐workers synthesized a series of first‐row transition metal/CdS nanosheets, including Mn, Fe, Co, Ni, and Cu supported on CdS, for the photocatalytic oxidation and degradation of lignin models . They revealed that Ni/CdS not only showed excellent catalytic performance for conversion of lignin into aromatic products in high yields but also simultaneously promoted H 2 evolution under visible light irradiation …”
Section: Catalysts For Photocatalytic Lignin Conversionmentioning
confidence: 99%
“…One-pot photocatalytic breaking of β-O-4 linkage through first oxidation of C α HOH by holes to produce ketone intermediates, followed by reductive cleavage of C β O bond was realized over ZnIn 2 S 4 [51] and Ni/CdS nanosheet. [52] Mechanistic studies revealed that the oxidation of the alcoholic group (C α HOH) by holes delivered ketone intermediates and protons, which were then reduced by electrons to hydrogen adsorbed on the surface of the catalyst. The hydrogen adsorbed on the surface could reductively break the C β O bond in the β-O-4 ketone intermediate.…”
Section: Depolymerization Of Lignin By Selective Co-bond Cleavagementioning
confidence: 99%